2021
DOI: 10.1002/nop2.1145
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of virtual reality simulation education based on coronavirus disease 2019 scenario for nursing students: A pilot study

Abstract: Aim This research is designed to establish and evaluate the effectiveness of a virtual reality simulation program using COVID‐19 scenario for nursing students. Design This is a quasi‐experimental study using a non‐equivalent control group pre‐test‐posttest design. Methods The participants were 65 students in their fourth year in nursing college. The knowledge about communicable infectious diseases in the respiratory system, self‐efficacy, clinical reasoning capacity and learning satisfaction was evaluated. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
0
14
2
Order By: Relevance
“…In both the control and intervention groups, significant differences were found in the nursing students’ knowledge about infectious respiratory diseases, self-efficacy, and clinical reasoning between the pre-test and post-test. However, no difference was found between the two groups [ 34 ], as was the case in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…In both the control and intervention groups, significant differences were found in the nursing students’ knowledge about infectious respiratory diseases, self-efficacy, and clinical reasoning between the pre-test and post-test. However, no difference was found between the two groups [ 34 ], as was the case in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…First, an immersive VR simulation (ie, COVID-19 VR Strikes Back) was at least as effective as traditional learning methods for training medical students regarding COVID-19–related skills [ 68 ]. Second, 2 immersive VR experiences, one involving wearing and stripping personal protective equipment [ 73 ] and the other involving the management of patients with respiratory infectious diseases due to COVID-19 [ 77 ], provided an effective and safe alternative to training nurses during the first year of the COVID-19 pandemic. Third, a virtual simulation of 2 patients (ie, COVID-19 and surgical trauma), which tried using desktop displays, helped nursing students bridge gaps in teaching and learning processes [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…These con icting results were probably because the students in the intervention group practically performed the intended roles and continued until mastery. Jeong et al (2022) showed that virtual reality simulation training based on the COVID-19 scenario was e cient. In both the control and intervention groups, signi cant differences were found in the nursing students' knowledge about infectious respiratory diseases, self-e cacy, and clinical reasoning between the pre-test and post-test.…”
Section: Karageorge Et Al (2020) Assessed the Skills Of Crisis Manage...mentioning
confidence: 99%